Factors associated with outcome of acute encephalitis in children: a retrospective study of three referral hospitals (Medical Journal of Indonesia, 2020)
BACKGROUND Encephalitis is more frequent in children and has a poor outcome. There was no data on encephalitis in children in Indonesia, so this study was aimed to evaluate clinical presentation and diagnostic examination of children with acute encephalitis, and factors related to outcome. METHODS This was a retrospective study of medical records between 2014 and 2018 in three referral hospitals in Jakarta and Tangerang. Clinical presentation at admission, cerebrospinal fluid analysis, neuroimaging, and electroencephalography (EEG) were documented. Outcome was determined at hospital discharge and classified as poor for severe neurological abnormalities at discharge or died. Logistic regression was used to evaluate associated factors with the outcome. RESULTS A total of 190 children were included and most were age >1 year (71%). Most subjects presented with fever (90%) and seizures (87%). Of those who had seizures, 80% experienced generalized seizures. Focal neurological deficit was seen in 90 patients (47%). EEG was positive in 90% subjects (n = 27/30). Probable cases were found in 51% of all subjects. The mortality was 23%. Focal seizures (odds ratio [OR] = 3.305, 95% confidence interval [CI] = 1.122–9.742) and age >1 year (OR = 3.076, 95% CI = 1.388–6.803) were risk factors for a poor outcome. CONCLUSIONS Acute encephalitis occurred most often in children aged >1 year. Fever and seizures were the most common symptoms. EEG was better than other examinations for confirming diagnosis of encephalitis. Focal seizures and age >1 year were associated with a three-fold increased risk for a poor outcome.